Simulator Respon Pesawat Berbasis Mikrokontroler: Media Edukatif bagi Siswa dan Komunitas Radio Kontrol - Buyung Junaidin; Djarot Wahju Santoso; Bambang Sudibya; Agung Prakoso; Makus Tri Wahyudi (Jurnal Pengabdian Masyarakat Sains Indonesia, 2025)
Interactive learning media are essential in aerospace engineering education, particularly for understanding flight control systems that are difficult to grasp through theory alone. Aircraft responses to aileron, elevator, and rudder deflections require clear visualization to help learners connect control inputs with changes in aircraft attitude. To address this need, this community service program developed a microcontroller-based aircraft response simulator equipped with an attitude sensor as an educational tool for students and radio control (RC) enthusiasts. The microcontroller processes real-time data from an Inertial Measurement Unit (IMU) and displays the aircraft’s attitude angles (yaw, pitch, and roll) on an LCD screen, allowing participants to directly observe how control inputs influence attitude changes. The miniature aircraft responds according to the displayed attitude angles, enabling learners to better understand the relationship between control inputs and aircraft dynamics. Evaluation results show that the simulator operates reliably, provides accurate attitude information, and significantly enhances participants’ understanding of flight control concepts and attitude dynamics. Users also reported that the simulator is easy to operate, engaging, and effective for foundational training in RC aviation. Thus, the microcontroller and IMU-based simulator serves as a practical, replicable, and modern learning medium aligned with contemporary aerospace education.